A mini-review on the insight into the effect of natural and Synthetic α,β-unsaturated carbonyl-containing compounds on PI3K/AKT/mTOR signaling pathways to treat breast cancer - Khai Voon, Kelvin Wong; Gazali, Ahmad Mahfuz; Zamri, Normaiza; Rullah, Kamal; Mohd Aluwi, Mohd Fadhlizil Fasihi (World Scientific, 2022)
Breast cancer, which has been one of the most frequently diagnosed cancers worldwide for decades, continues to defy treatment. While researching a remedy to this problem, it was discovered that mTOR has a strong association with breast cancer. Uncontrolled activation of mTOR is shown in a variety of different cancer, making it a critical target for cancer treatment. Inhibition of the mTOR protein kinase can cause autophagic cell death. It is known that covalent inhibitors have become a prominent issue in drug discovery, with covalent inhibitors focusing on ; -unsaturated carbonyl molecules. Structural modifications to ; -unsaturated carbonyl may be one of the finest avenues for developing the best breast cancer medication. This review article discusses recent research on natural and synthetic ; -unsaturated carbonyls and their anti-cancer properties targeting on mTOR, with SAR to showcase the efficacy of synthetic natural products compared to parental compounds using both biological assays and in silico studies.